Oi Herra, luoksein jää : hengellisiä lauluja - Timotei (naiskuoro); Ahtiainen, Lauri; Heroja, Matti; Hieta, Reetta; Peltovuori, Reetta; Kivikoura, Anneli; Perko, Pekka; Lopen lapsi- ja nuorisokuoro (Musiikin Tuki Loppi / Pekka Perko, 1999)
29 kappaletta.
Keywords: nuorisokuorot